An island model based genetic algorithm for solving the capacitated vehicle routing problem - Ammi, Meryem; Chikhi, Salim (2014 6th International Conference of Soft Computing and Pattern Recognition (SoCPaR), 2014)
The present work proposes an island model for solving the capacitated vehicle routing problem. The developed approach consists of using a paradigm called the island model that rules the cooperation held by different islands. Each island performs a genetic algorithm for solving the problem in subject and exchanges solutions with other islands via the migration operator. The genetic algorithm used on each island uses different recombination parameters in order to interplay the intensification and the diversification of the search space. Tests over the different known benchmarks in the literature have resulted very promising results. Demonstrating the efficiency of the proposed approach and offering new perspectives.